SIMULAÇÕES DE TRANSPORTE REATIVO EM UM AQUÍFERO CONTAMINADO POR QUEROSENE DE AVIAÇÃO - Teramoto, Elias Hideo; Chang, Hung Kiang; Baessa, Marcus Paulus Martins; Soriano, Adriana (Geochimica Brasiliensis, 2019)
The ability of native bacteria to biodegrade sub-surface hydrocarbons has been studied consistently since the 1970s, since this class of contaminants may pose severe human health risks. Understanding the mechanisms that govern hydrocarbons biodegradation represents a crucial issue for the management of contaminated areas. For this reason, numerical simulations of reactive transport were performed to evaluate the conceptual geochemical model and to help understand the mechanisms that govern BTEX biodegradation in a lateritic aquifer contaminated by large aviation fuel. The feasibility of previously proposed conceptual model linking geochemical zonation with BTEX mineralization and secondary reactions was evaluated by means of reactive transport models. The representation of the simulated chemical speciation of the studied hydrocarbon-contaminated aquifer is best supported when PCO2 is fixed and dissolved oxygen, potentially present due to mass transfer from entrapped air, is considered in the model. These findings suggest the need for both constraints to be considered in the reactive transport models involving hydrocarbon biodegradation.